The Synthesis of 2-Thiohydantoin Derivatives in the Presence of Ionic Liquid (1-Decyl-3-Methylimidazolium Bromide, [C10MIM][Br]) Using Microwave Assisted Organic Synthesis (MAOS) Method - Suparno Putra, Ismail
2-Thiohydantoin is the analogue of hydantoin derivative compounds by replacing the oxygen atom of the carbonyl group with a sulfur atom in position number two of hydantoin ring. 2- Thiohydantoin derivative compounds have several valuable applications in the health field as anti-mutagenic, anti-cancer, anti-proliferative, anti-angiogenic, and anti-malarial. The synthesis of 2-thiohydantoin derivative (5-(4-hydroxybenzyl)-2-thiohydantoin) was carried out by reacting L-tyrosine with tiourea via condensation reaction. However, in this research, the synthesis of 2-thiohydantoin was performed in the presence of ionic liquid 1-decyl-3- methylimidazolium bromide ([C10MIM] [Br]) as reaction medium. The synthesis of ionic liquids 1-decyl-3-methylimidazolium bromide and 2-thiohidantoin were performed using MAOS (Microwave Assisted Organic Synthesis) method. The ionic liquid 1-decyl-3- metlimidazolium bromide was synthesized by reacting 1-methylimidazole with 1- bromodecane at a temperature of 50 °C with microwave irradiation power of 300 watts for 21 minutes. The ionic liquid 1-decyl-3-methylimidazolium bromide was obtained in the form of a yellow colored viscous liquid with a melting point of 31 °C and the yield of 83.53%. The characterization of product using the analysis of FTIR spectra data with KBr pellets, mass spectrum of product (via LC-MS measurement in methanol), and 1H-NMR and 13C-NMR spectra of product in methanol-d4 showed that the ionic liquid 1-decyl-3-methylimidazo l ium bromide has been successfully synthesized. The synthesis of 2-thiohydantoin derivative was carried out by reacting L-tyrosine with tiourea in the presence of ionic liquid 1-decyl-3- methylimidazolium bromide as reaction medium using the variations of microwave irradiation power (300-600 watts). According to the results of several experiments in various conditions , the optimal microwave irradiation power was obtained at 300 watts that produced the desired product with the yields of 23.69% at a temperature of 49 °C for 38 seconds with melting point of 203-206 °C. The characterization of product using the analysis of FTIR spectra data with KBr pellets, mass spectrum of product (via LC-MS measurement in methanol), and 1H-NMR and 13C-NMR spectra of product in acetone-d6 showed that 2-thiohydantoin derivative compound (5-(4-hydroxybenzyl)-2-thiohydantoin) has been successfully synthesized.